How to utilize natural regeneration of birch to establish mixed spruce-birch forests in Finland? - Männistö, Lauri; Miina, Jari; Huuskonen, Saija (Suomen metsätieteellinen seura, 2024)
Mixed forests are known for their ability to provide a wide range of ecosystem services. Such forests have higher biodiversity compared to monocultures, are resilient against disturbances and may mitigate the effects of climate change. Despite well-known benefits, there is still little information on how these forests should be established and managed. The aim of this study was to describe the early growth dynamics of current boreal young mixed stands of planted Norway spruces (Picea abies (L.) Karst.) and naturally regenerated birches (Betula spp.). We collected data from 9 stands planted for spruce 8–14 years ago in southern and central Finland. Stem analysis was conducted to 144 spruces and to 144 birches to determine previous growth. We modelled the height and diameter development of individual trees in relation to tree age at stump height using non-linear mixed Chapman-Richards model. There were no significant differences between spruce and seed-origin birch in diameter growth at stump height, but the initial height increments of natural birches were larger than those of planted spruces. However, planted spruces were able to keep up with the height development of birches, if spruces received a head start over naturally regenerated seed-origin birch for two growing seasons. Thus, naturally regenerated birch admixture can be utilized to establish single-storied spruce-birch mixtures, and the admixture should be retained during the early cleaning of planted spruce stands.
Keywords: sekametsät; metsäkuusi; rauduskoivu; hieskoivu